Politicised Parables: A Reassessment of Bonnie Ntshalintshali's Early Ceramic Sculptures. Issue 1 (2nd January 2022) - Richards, Christopher
Abstract: As ceramics by Black South African artists garner increased academic interest, the work of early Ardmore Design artists, exemplified by Bonnie Ntshalintshali, remain on the periphery of scholarly investigation. This article seeks to reacquaint the art historical community with Ntshalintshali's sculptural works, demonstrating the cultural and historical relevance of her ceramics as potent expressions of her unique perspective and artistic voice. With a focus on early artworks inspired by Christian parables, this exploration of specific sculptures elucidates Ntshalintshali's relationship with Christianity, fused with her Zulu heritage and Black South African identity. By examining these works as interconnected, as opposed to singular masterpieces, common themes and repeated motifs become evident. Ultimately, this article provides a more nuanced and extensive assessment of a selection of Ntshalintshali's sculptural forms, illustrating their complexity, their thoughtful and potent imagery, and their embodiment of complex personal narratives.